Analyzing the role of risk mitigation and monitoring in software development - Kumar, Rohit, 1986- (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2018)
"This book captures the latest research and innovations and case studies in the field of software development risk management. A number of tools, methods, processes alongside theoretical concepts have been mentioned to manage and control software development risks"--